New efforts? A competence-oriented task analysis of interlingual live subtitling - Pöchhacker, Franz; Remael, Aline (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2020)
This article offers a theoretical analysis of interlingual live subtitling as a translational task with the aim of defining the skill set and competence profile to be developed by future practitioners. The outcome of this task analysis will thus serve to guide curriculum design both for training in interlingual live subtitling and for developing task-specific teaching methods. While taking account of the findings of empirical studies conducted in the context of the EU-funded Erasmus+ project, Interlingual Live Subtitling for Access[i]and related research, our line of argument is essentially deductive: models of the interpreting process and of translational competence are our essential points of departure. Our process analysis of interlingual live subtitling, which refers to the Effort Model, will identify subprocesses and subskills. The latter will be put together in a competence model as a framework that can be filled with specific learning outcomes for training in interlingual live subtitling. [i] This research was carried out within the framework of the European ILSA Project (for further information see www.ilsaproject.eu), though it was not part of the funded Intellectual Outputs of the project. We would like to thank our ILSA partners for their critical reading of the draft version of this article and their constructive input.